Advantage of laparoscopic surgery in patients with generalized obesity operated for colorectal malignancy: A retrospective cohort study - Yu, Yen-Lin; Hsu, Yu-Jen; Liao, Chun-Kai; Lin, Yueh-Chen; You, Jeng-Fu; Tsai, Wen-Sy; Jong, Bor-Kang; Chern, Yih-Jong (Frontiers in Surgery, 2023)
Background: Because of the progression of minimally invasive surgery skills and obesity in colorectal surgery, we aimed to evaluate the short-term outcomes of colorectal cancer resections in patients with generalized obesity at a single teaching hospital with mature surgical techniques and training programs. Methods: A total of 537 patients were diagnosed with CRC and had a body mass index ≥30 kg/m2 between January 2009 and December 2019 at a single institution. 265 patients underwent open surgery and 272 patients underwent laparoscopic surgery. Data were analyzed to explore the independent risk factors for postoperative complications. Results: The laparoscopic group had less blood loss (73 ± 128 mL vs. 148 ± 290 mL, p < 0.001) and a shorter postoperative hospital stay (10.8 ± 17.1 days vs. 11.7 ± 6.8 days, p < 0.001) than the open group. The number of harvested lymph nodes did not significantly differ between the two groups (30.9 ± 18.3 vs. 30.2 ± 15.3, p = 0.981). Although anastomotic leakage was significantly higher in the laparoscopic group (1.5% vs. 4.8%, p = 0.030), there were also similar overall postoperative morbidity and mortality rates between the open and laparoscopic groups for CRC patients with generalized obesity who underwent surgery. Conclusions: Laparoscopic surgery can reduce blood loss, decrease the length of hospital stay, obtain a similar number of harvested lymph nodes, and achieve an acceptable conversion rate for CRC patients with generalized obesity. We suggest that laparoscopic surgery could become a standard method for CRC treatment in patients with generalized obesity.